Realisasi Pengendalian Emosi Diri dengan Konsep Stoisisme dan Tasawuf - Ajeng Maelany (Gunung Djati Conference Series, 2022)
Abstract This study aims to discuss the relationship of emotional self-control with the concept of Stoicism and Sufism. This study uses a qualitative approach by applying a descriptive-analytical method. The formal object of this study is the concept of Stoicism and Sufism, while the material object is self-emotional control. The results of this study indicate that there is a relationship between Frager's thinking and Stoicism which has different concepts. Each thought has distinct differences, such as the stoic wisdom introduced by Manampiring and the Eastern-style Sufistic wisdom by Frager. This study concludes that Sufism and Stoicism both meet at the same estuary, namely the importance of controlling human perception in dealing with problems or stimuli that are in front of them.